Role of a prolonged inpatient admission when evaluating children with problematic severe asthma. Issue 2 (1st February 2018) - Nagakumar, Prasad; Gambir, Nikki; Sanghani, Nina; Hall, Pippa; Jamalzadeh, Angela; Beresford, Frances; Saglani, Sejal; Bush, Andrew; Fleming, Louise
Severe asthma continues to be a significant cause of morbidity in children. Despite optimised standard therapy, many children remain symptomatic with subsequent impact on their quality of life and increased healthcare utilisation [1]. Children with ongoing poorly controlled asthma despite maximally prescribed treatment are identified as having problematic severe asthma [2]. Those whose poor control is due to modifiable factors including poor adherence to medications, continued exposure to allergens, social issues and psychological factors have difficult asthma. Severe therapy-resistant asthma is the term used for those with persistent symptoms despite attention to the basics of asthma management [3]. Valuable information can be obtained during inpatient assessment of children with problematic severe asthma http://ow.ly/RiKc30hzNXz